Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1118/1.3120286
|View full text |Cite
|
Sign up to set email alerts
|

Fast convolution‐superposition dose calculation on graphics hardware

Abstract: The numerical calculation of dose is central to treatment planning in radiation therapy and is at the core of optimization strategies for modern delivery techniques. In a clinical environment, dose calculation algorithms are required to be accurate and fast. The accuracy is typically achieved through the integration of patient-specific data and extensive beam modeling, which generally results in slower algorithms. In order to alleviate execution speed problems, the authors have implemented a modern dose calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 18 publications
1
56
0
Order By: Relevance
“…Recently, the rapid development of GPU technology for scientific computing has offered a promising prospect to speed up computationally heavy tasks in radiotherapy. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Although GPU has been utilized in the TNLM-based 4D-CT reconstruction study, the implementation was not optimal. A new implementation of the algorithm in the 4D-CBCT context is necessary to fully explore the GPU's computational power.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the rapid development of GPU technology for scientific computing has offered a promising prospect to speed up computationally heavy tasks in radiotherapy. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Although GPU has been utilized in the TNLM-based 4D-CT reconstruction study, the implementation was not optimal. A new implementation of the algorithm in the 4D-CBCT context is necessary to fully explore the GPU's computational power.…”
Section: Introductionmentioning
confidence: 99%
“…11) GPU clusters are more affordable and require lighter maintenance than traditional CPU clusters. GPU algorithms have been used for dose calculations by Hissoiny et al 12) and Jacques et al, 13) who implemented superposition convolution algorithms for dose calculations on GPUs. A GPU-based Monte Carlo code for coupled electron-photon transport was implemented by Jia et al, 14) who reported a calculation time reduction up to a factor of 6.6.…”
Section: Introductionmentioning
confidence: 99%
“…The acceleration factor provided by general purpose parallel computing on graphical processing units [57][58][59][60][61] has made the method applicable. Following implementation for external beam treatment planning, Oncentra® Brachy v. 4.4 (Nucletron, an Elekta company, Veenendaal, Netherlands) was released in 2013 including the capability for 192 Ir dosimetry calculations based on the CCS method, under the commercial name Oncentra-ACE (Advanced Collapsed cone Engine).…”
Section: Collapsed Cone Superposition: Clinical Implementationmentioning
confidence: 99%